Spam e-mail: how Malaysian e-mail users deal with it? - Bujang, Yanti Rosmunie; Hussin, Husnayati (2010)
This paper attempts to discuss the spam issue from the Malaysian e-mail users’ perspective. The purpose is to discover how Malaysian users handle the spam e-mail problem. From the experiences we hope to discover the necessary effort needed to be undertaken to face this problem in the context of Malaysia. A survey was conducted to understand how Malaysian individual perceived spam and what they actually do with the spam e-mail they received in their daily life. The findings indicate that the level of awareness on spam issue in action is still low and need some extra effort by government and relevant agencies to increase their level of awareness. Keywords – e-mail, Malaysia, spam, users’ perspective